Optimizing position-wise anthropometric models for prediction of playing ability among elite Indian basketball players - Viswanathan, J.; Chandrasekaran, K. (International Journal of Sports Science and Engineering, 2011)
The purpose of this study was to predict the role of a number of anthropometric characteristics in performance of Indian youth elite Basketball players with special reference to their playing positions. Two hundred and seventy six (age, 15.1 ± 1.3 years) youth elite male Basketball players from 23 states of India participated in the 26th Lakadawala Youth National Basketball Championship at Mastan YMCA, Mumbai from 9th to 16th May 2009, were selected as the subjects. The selected subjects were divided into three groups according to their playing positions namely Guard (GD = 72), Forward (FD = 126) and Centre (CR = 78). The selected anthropometric variables namely Body weight, Skinfold measurements (mm) - Biceps, Subscapular, Triceps, Supraspinale, Abdominal, Illiac Crest, Front Thigh and Medial Calf; Girth measurements (cm) - Arm girth relaxed, Arm girth flexed and Calf girth; Length measurements (cm) - Standing height, Arm span, Arm length, Leg length and Breadth measurements (cm) - Humerus breadth and Femur breadth as the independent variables were taken for this study. The data were collected by following standard testing protocal of International Society for the Advancement of Kinanthropometry (ISAK) during the competition by scientifically approved equipments. The criterion variable, playing ability of the selected Basketball players are assessed by three qualified Basketball coaches. To determine the relationship between the selected anthropometric variables and the coaches rating on playing ability, the coefficient of correlation was used. Anthropometric variables that statistically correlated with performance were used to form respective linear predictive models (stepwise argument selection) with special reference to their playing positions for predictive equation development. The results revealed that there was a strong correlations (r = 0.9) exists between the playing ability versus height, weight, arm length, arm span, leg length and flexed arm girth among all the playing positions.